Corporate governance and financial performance - a study of the Indian drug and pharmaceutical industry. (25th July 2022) - Shah, Avani; Paliwal, Udai Lal
Issues surrounding corporate governance practices assumed greater significance over the past few decades as research has proven that good corporate governance significantly influence performance of companies. Using panel data from 90 listed companies of the Indian drug and pharmaceutical industry for a period of five years (2015 to 2019), the present paper analyses the influence of corporate governance on financial performance of the sample companies. Return on assets (ROA) and return on capital employed (ROCE) were used to measure financial performance. The study revealed a mixed impact as promotor shareholdings, CEO duality and firm size were positively and significantly related to firm's financial performance, however, board independence, board size, leverage and liquidity were found not to have a significant impact. This study is useful as it provides some useful insights on the envisaged relationship in a specific context of the Indian drug and pharmaceutical industry.